Topic familiarity and extraversion in ESL oral assessment: a conceptual review - Ahmad Bukhari, Nurul Iman; Ismail, Lilliati; Abu Kassim, Noor Lide; Noordin, Nooreen; Razali, Abu Bakar (Human Resources Management Academic Research Society (HRMARS), 2024)
Oral performance among test-takers in proficiency English tests has shown to be prone to variability due to its rater-mediated nature. Test-takers could better lead their assessment preparation if they understood more about how to optimise their strengths, which can be identified as test-taker characteristics. The purpose of this study is to determine whether topic familiarity and extraversion can be linked to oral assessment facets using the Conceptual-psychometric framework of rater-mediated assessment (Eckes, 2015). To understand how these factors affect test performance and task engagement, it focuses on the relationship between test takers’ topic familiarity and extraversion traits. By reviewing existing literature, this review proposed a conceptual framework that explains the concepts inherent in ESL oral assessment to investigate test-taker individual differences in topic familiarity and extraversion. This review seeks to contribute to a deeper understanding of how these factors interact and may influence the results of ESL oral assessments by carefully examining the relationships between individual differences such as topic familiarity and extraversion and oral assessment. Furthermore, it displays the significance of involving affective and cognitive dimensions of test-taker behaviour when developing assessment instruments that are dependable and valid for English as a Second Language (ESL) learners. Future research directions and the implications of these findings for ESL assessment practices are also addressed.